Caracterização da família multigênica da oxidase alternativa em plantas do gênero Medicago e avaliação da expressão em Medicago sativa sob condições de estresse - Cavalcanti, João Henrique Frota (2011)
In plants, Alternative Oxidase (AOX) is enconded by small milti gene family located in genomc DNA. This multi gene family was studied in mono and dicots plants being clusterd in two subfamilies: Aox1 and Aox2. Aox1 gene are found in all angiosperms táxon presenting gene expression related to stress situations while Aox2 genes are found in dicots plants only and presenting a houkeeping expression. Many Aox1 genes e just one Aox2 are found in the most of dicots studied. However, in Fabales, as cowpea and soybean, is found a profile with two genes Aox2 (Aox2a , Aox2b) and one Aox1 gene. In this work was characterized a multi gene family of Aox genes in Medicago genus (Medicago truncatula e Medicago sativa) belonging to Fabales Order. Data mining in genBanks characterized four Aox genes (Aox1, Aox2a, Aox2b1 and Aox2b2) in Medicago truncatula genome revealing for first time a duplication of Aox2b genes. Specifics primers designed for each Aox gene and then were used to amplification by PCR, cloning and partial sequencing of these genes in Medicago sativa. Gene expression was carried out by semiquantitative RT-PCR in: germination seeds (0, 24, 48 hours of germination), roots and leaves from Medicago sativa grewth in Hoaglend’s medium and applied to disticts stress conditions (0, 6, 12 e 24 hs after treatment): control, salicylic acid (0,5mM), PEG (100g/L), H2O2 (10mM) e cisteíne (0,5mM). The results revealed that all four Aox genes were detected in seed of Medicago sativa. However, Aox1, Aox2b1 and Aox2b2 genes presented high expression during germination while Aox2a showed constitutive expression. In leaves, Aox1, Aox2a and Aox2b1 were detected in all conditions tested, but Aox2b2 was observed more strong in stress situations only. Simirily observed in germination, Aox1, Aox2b1 and Aox2b2 increased transcripts levels in response to all stress conditions. Aox2a, one more time, had constitutive, but very strong expression. In roots, all genes were detected and a similar induction profile of Aox1, Aox2b1 and Aox2b2 were confirmed less to PEG treatment where just Aox1 was responsive. Aox2a had constitutive expression too, but it was weakly expressed. In order to understand the co-expresion of Aox1, Aox2b1 and Aox2b2 genes, the promoter regions were cloned and sequenced revealing close motifs among them suggesting th involviment of cis-elements in their regulation. Theses resuls corroborate with co-expression stress-induced of Aox1/Aox2b found in cowpea. However, in Medicago sativa, it was observed tissue-specific exression. Aox1, Aox2a and Aox2b1 with characteristics constitutive and induced in seeds germination and roots tissue while in leaves Aox2b2 differed by present stress-induced expression only.